Analysis of Velocimetry Processing Method Based on Doppler Asymmetric Spatial Heterodyne Spectrometer - Xiang Peng; Enhai Liu; Shulin Tian; Rujin Zhao (IEEE Photonics Journal)
The Doppler Asymmetric Spatial Heterodyne (DASH) spectrometer is a new type of high-resolution spectral measurement instrument that has received widespread attention in re-cent years. However, in previous ground experiments, laser sources were often used so that without exposing the premise and limitations of its high measurement accuracy. Therefore, this article provides a detailed introduction to the measured physical quantity transfer process, de-rives the constraints of DASH spectral velocimetry by discrete sampling, spectral offset analysis, and phase deviation analysis methods. Furthermore, it clarifies the impact of back-end signal processing methods on velocity measurement resolution and the range of algorithm errors. With a “spring model” of interference fringes is proposed, which not only provides mathematical model support for the superiority of using phase shift measurement methods to invert Doppler velocity, but also explains the improvement reason of the “asymmetric” structure relative to the original symmetric spatial heterodyne spectrometer. Meanwhile, based on the simulation values of the set parameters, the measurement resolution improvement factor of the interferometric phase measurement method relative to the spatial frequency measurement method is quantitatively calculated. In the field of astronomical remote sensing, due to stellar spectra lack of the monochromaticity and ideal spectral shape of laser sources used in ground experiments, it is necessary to consider whether the specific characteristics of the incident spectrum meet the amplification effect and effective range on the measured physical quantity transmission chain. It provides a reference for the practical application of the DASH spectral velocimetry technology.